Analyzing The Use of Dompet Dhuafa and Kitabisa.com Online Fundraising Platforms in Promoting Millennial Philanthropy - Farid, Muhammad Rifa'at Adiakarti; Andriani, Kiki; Najib, Labud Nahnu; Khoirulika, Rizka (Palita: Journal of Social Religion Research, 2025)
Crowdfunding is a new strategy used by social service institutions, such as Dompet Dhuafa, to facilitate donations, charity, and online giving of alms. One platform that enables this is kitabisa.com, a forum for individuals, communities, or social service organizations that wish to raise funds through online donations with various goals, one of which is donation. This paper aims to discuss the Dhuafa wallet, which invites millennials to donate and educate themselves on humanitarian values through the crowdfunding platform kitabisa.com. Additionally, Dompet Dhuafa aims to utilize social media in its crowdfunding mechanism, targeting other digital users. This research is a qualitative descriptive study. Primary and secondary data sources were collected through observation, interviews, documentation, and online data searches. The data collected is processed and analyzed to describe the level of effectiveness of implementing a financial technology-based zakat payment system in Yogyakarta, specifically at Dompet Dhuafa. The results of this study indicate that social media and millennials grow in the presence of a crowdfunding platform. Additionally, the crowdfunding mechanism implemented by Dompet Dhuafa offers solutions for millennials to donate practically and lawfully.